Bibliometric Analysis of Artificial Intelligence - Rohimatun Nur’aeni; Rendy Zalsahra (West Science Interdisciplinary Studies, 2024)
Artificial Intelligence Bibliometric Analysis (AI) is a study involving quantitative measurement and evaluation of scientific literature on artificial intelligence. Relevant keywords in this analysis include "artificial intelligence", "machine teaching", "deep training", and "This method allows researchers to identify major developments and focus in artificial intelligence research, provide insight into the authors' contributions, and understand the direction of this science. Artificial intelligence is a branch of computer science that focuses on developing computing systems that can perform tasks that normally require human intelligence. Using algorithms and mathematical models, AI can process data quickly, identify patterns, and make intelligent decisions.AI development has created applications that have changed the way we work, learn, and interact. From efficient automation systems to virtual assistants that understand and respond to human conversations, AI has made significant contributions to improving productivity and quality of life. We use VOSviewer software to classify the material after reviewing the database.